Pengaruh Laju Alir CO2 Dan Suhu Pada Proses Presipitasi Silika Dengan Menggunakan Dispersan Polietilen Glikol - Novi Purnama; Edy Saputra; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Precipitated silica can be synthesised from Palm Mill Oil Fly Ash (POMFA) by alkali extraction combined with sol-gel precipitation. Sodium hydroxide were used to extract silica from POMFA to produce sodium silicate. Silica was precipitated using CO2, the effect of CO2 flow rate and temperature on the precipitation process were studied. The CO2 flow rate of 100, 200, 300 and 400 mL/min and temperature of 60.70, 80, 90oC were used at the precipitation process, to enhance the characteristic of precipitated silica obtained, dispersant PEG-400 5% (v/v) was added. The CO2 flow rate was stopped when the silica began to precipitate and the stirring speed increase up to 1000 RPM for 90 minutes. Silica obtained, was separated from the filtrate using filter paper, washed with hot distilled water and then dried. The maximum yield of 81.01% was obtained at temperature of 70oC and a flow rate of 200 mL/min. The precipitated silica was characterised using XRF to determine silica composition and XRD to determine wether the precipitated silica is in amorphous form. The Scherrer equation was applied to estimate the primary particle diameter.Keywords: CO2, Precipitated, Silica, Temperature, Yield